The effect of wave conditions and surfer ability on performance and the physiological response of recreational surfers - Barlow, M. J.; Gresty, K.; Findlay, M.; Cooke, C. B.; Davidson, M. A. (The Journal of Strength and Conditioning Research, 2014)
This study investigated the effects of wave conditions on performance and the physiological responses of surfers. After institutional ethical approval 39 recreational surfers participated in 60 surfing sessions where performance and physiological response were measured using global positioning system (GPS) heart rate monitors. Using GPS, the percentage time spent in surfing activity categories was on average 41.6, 47.0, 8.1, and 3.1% for waiting, paddling, riding, and miscellaneous activities, respectively. Ability level of the surfers, wave size, and wave period are significantly associated with the physiological, ride, and performance parameters during surfing. As the ability level of the surfers increases there is a reduction in the relative exercise intensity (e.g., average heart rate as a percentage of laboratory maximum, rpartial = -0.412, p < 0.01) which is in contrast to increases in performance parameters (e.g., maximum ride speed (0.454, p < 0.01). As the wave size increased there were reductions in physiological demand (e.g., total energy expenditure rpartial = -0.351, p = 0.05) but increases in ride speed and distance measures (e.g., the maximum ride speed, 0.454, p < 0.01). As the wave period increased there were increases in intensity (e.g., average heart rate as a percentage of laboratory maximum, rp = 0.490, p < 0.01) and increases in ride speed and distance measures (e.g., the maximum ride speed, rpartial = 0.371, p < 0.01). This original study is the first to show that wave parameters and surfer ability are significantly associated with the physiological response and performance characteristics of surfing.